Strengthening Child Mental Health Through Family-Centered Islamic Religious Education - Deitra Vania Adellya Phasya; Purwidianto Purwidianto (Jurnal Iman dan Spiritualitas, 2026)
This study examines how family-based Islamic religious education supports children’s mental health amid modern social pressures such as digital exposure, academic stress, and changing values. Using a qualitative literature review and thematic analysis of national and international sources, the research shows parents centralize psychological well-being by transmitting faith (aqidah), worship (ibadah), moral values (akhlaq), and compassionate parenting. These practices foster emotional regulation, self-confidence, coping skills, empathy, gratitude, resilience, and secure parent–child attachment, reducing anxiety and other difficulties. The study frames family Islamic education as both moral-spiritual formation and a protective factor for children’s mental health, offering a conceptual basis for family-centered strategies that integrate psychological and spiritual care.